2022
DOI: 10.5430/wjel.v12n8p86
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of Social Networking Sites for English Language Learning: A Study in an Indonesian Higher Education Context

Abstract: This study explores the use of Social Networking Sites (SNS) as a performance-enhancing method of teaching and learning of English in the classroom via cell phones and mobile devices, as well as its effect on students' motivation to learn. A survey was disseminated to 176 students. The analysis showcases that Instagram is the most useful learning tool that students enjoy, and its use on mobile devices has the potential to become a significant teaching tool in the classroom. Because the most popular social netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Study results showed that social media had a significant effect in improving and developing English competence and skills in this technological era. Additionally, Tambunan et al (2022) investigated the impact of social media as a mobile phone-based classroom teaching and learning method on students' English proficiency and motivation to learn. They found that students were already using social networking sites informally to enhance their learning.…”
Section: Introductionmentioning
confidence: 99%
“…Study results showed that social media had a significant effect in improving and developing English competence and skills in this technological era. Additionally, Tambunan et al (2022) investigated the impact of social media as a mobile phone-based classroom teaching and learning method on students' English proficiency and motivation to learn. They found that students were already using social networking sites informally to enhance their learning.…”
Section: Introductionmentioning
confidence: 99%